S43 Hypoxia upregulates PI3KINASE-dependent neutrophil degranulation and neutrophil-mediated tissue injury. (15th November 2016) - Lodge, KM; Hoenderdos, K; Robbins, AJ; Storisteanu, DM; Chilvers, ER; Li, W; Condliffe, AM
Abstract : Introduction: Damage to host tissue from persistent neutrophilic inflammation is implicated in the pathogenesis of many diseases, including chronic obstructive pulmonary disease (COPD). Infected/inflamed tissues can be profoundly hypoxic; this state may synergise with inflammatory cytokines to promote a destructive neutrophil phenotype with enhanced potential for tissue damage. Methods: Neutrophils isolated from COPD patients or healthy volunteers were incubated under normoxia (21% O2) or hypoxia (0.8% O2) before treatment with priming (GM-CSF/PAF/TNF-α) and stimulating (fMLP) agents, with/without PI3Kinase inhibitors (pan/γ/δ). Neutrophil elastase (NE) activity was measured by Enzchek® assay. Western blotting for total and phosphorylated Akt was performed using cell lysates. Neutrophil extracellular trap (NET) production was assessed by fluorescence absorbance. Neutrophil supernatants were incubated with primary human pulmonary artery endothelial cells (HPAEC); death and detachment were measured by MTT assay and confocal microscopy. Precipitated neutrophil supernatants were separated by SDS polyacrylamide gel electrophoresis (PAGE) and silver stained. S100A8/A9 homo- and heterodimer content of neutrophil supernatants was assessed by ELISA. Results: Hypoxia increased NE release in an agonist- and PI3K-γ-dependent manner, with more pronounced hypoxic degranulation responses seen in exacerbating COPD patients. Hypoxia augmented resting and cytokine-stimulated Akt phosphorylation; PI3K-γ inhibition abrogated Akt phosphorylation and prevented the hypoxic uplift of NE release. Hypoxia did not increase NET production in resting or GM-CSF/fMLP treated cells. Hypoxic neutrophil supernatants induced extensive HPAEC detachment and death, which was prevented by co-incubation with alpha-1 antitrypsin. Silver stained protein bands from precipitated neutrophil supernatants separated by SDS-PAGE were identified by mass spectrometry, suggesting a hypoxic increase in damage associated molecular pattern (DAMP) proteins S100A8 and S100A9. When interrogated by ELISA, there was no difference between the amount of S100A8/A9 hetero- or homodimers in normoxic versus hypoxic supernatants. Conclusion: Hypoxia augments neutrophil degranulation in an agonist- and PI3K-γ-dependent manner, which may be further increased during COPD exacerbations. Hypoxic neutrophil supernatants have enhanced capacity to damage endothelial cells in vitro, likely due to increased release of NE. The contribution of S100A8/A9 proteins to this damage is currently unclear. Hence, hypoxia promotes a destructive histotoxic neutrophil phenotype with potential relevance to diseases such as COPD.